An Overview on Natia Aggregation" Madh-e- Rasool (SAWW) "in the form of Sanat –E Atila - Hina Tosief; Dr. Sadaf Naqvi (Zaban-o-Adab, 2022)
The writers and the poets of Urdu literature showed their skills in “Sanat-E-Atila” in both forms: “Nazam and Nasar”. In Urdu literature, the samples of “Sanat-E-Atila” are presents in “Quran, Tafaseer, Seerat nigari, Ghazal, Qaseeda, Marsia, and in other forms of poetry. Especially, the poets arranged aggregations (majmua) of Hamdia and Natia poetry. The “Midh-E Rasool (S.A.W)” by Raghab Murad Abadi got a distinguished status in the Natia Majmoa of Sanat E Atila. There are 40 Naats and 23 Rubayan in the whole book. The complete book is revolving around the seventeen ghair manqoot words. His expression of love in the challenging Sanat like Sanat E Atala is the obvious proof of his Ishq towards the Holy prophet(PBUH). His passion of love and devotion towards the Holy prophet (PBUH) can be seen on each and every page of this book “Midhe E Rasool”(S.A.W). His “Natia majmoa” is a masterpiece for Scholars, writers, researcher, and pure hearted peoples and a source of salvation on the Day of Judgment.